9 Epidemiology of neck injuries accompanying 3, 040 paediatric sport concussions in colorado over a 13-year period in a university-based healthcare system. (19th April 2018) - Carmichael, Joel; Staton, Elizabeth; Blatchford, Patrick; Stevens-Lapsley, Jennifer
Abstract : Objective: The same trauma producing a concussion may also produce a neck injury. The signs of concussion and neck injury are similar, and symptoms after acceleration-deceleration trauma to the head-neck complex do not accurately discriminate between them. Research on the epidemiology of neck injury among sport-concussed youth is sparse. This study describes the prevalence and probability of neck injury among concussed and sport-concussed youth by age, sex, and sport. Methods: This descriptive epidemiological study used aggregate data from de-identified, community-based electronic health records over 13 years to analyse rates and characteristics of neck injuries among youth aged five to 21 sustaining a sport-related concussion (SRC). Results: A total of 16 885 concussions were examined, of which 3, 040 SRCs in youth aged five to 21 were identified. Of the SRCs, 220 were accompanied by at least one neck injury diagnosis, with highest prevalence at age 14. For both sexes combined, the top four sports for concussion were American football, soccer, basketball and softball. By contrast, the top four sports for neck injury among concussed youth for both sexes was swimming, equestrian, snowboard and volleyball. Conclusions: The overall prevalence of diagnosed neck injuries among SRCs in the study population was 7%, with the highest prevalence at age 14 in both sexes. Sports with the highest rate of concussion differ from those with the highest prevalence of concussion-related neck injury in both sexes. The risk and prevalence of neck injury associated with SRC was higher in females.